ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKSUAL BERISIKO PADA ANAK BUAH KAPAL (ABK) DALAM PENULARAN PENYAKIT HIV/AIDS - Takesi Arisandy (NHM PRESS, 2022)
HIV/AIDS transmission occurs in all life lines. This condition can occur in any field of work, including for a sailor such as ABK (Crew). Several factors related to risky sexual behaviors in ABK such as condom use, attitudes, co-worker support, and encouragement of Women Sex Peddlers (WPS). To find out what factors are related to Risky SexualBehavior in The Crew. Literature Review method with journal search using google scholar published in 2011-2019. Based on the literature selection obtained 6 articles published. Of the 6 articles published, there are 4 articles stating the relationship of condom use factors, 3 articles about attitude factors, 2 articles there is a relationship of co-worker support factors, and the other is the push factor Of Women Sex Peddlers (WPS).